The scarlet gospels - Barker, Clive, 1952- (St. Martin's Press, 2015)
The Scarlet Gospels takes readers back many years to the early days of two of Barker's most iconic characters in a battle of good and evil as old as time: The long-beleaguered detective Harry D'Amour, investigator of all supernatural, magical, and malevolent crimes faces off against his formidable, and intensely evil rival, Pinhead, the priest of hell. Barker devotees have been waiting for The Scarlet Gospels with bated breath for years, and it's everything they've begged for and more. Bloody, terrifying, and brilliantly complex, fans and newcomers alike will not be disappointed by the epic, visionary tale that is The Scarlet Gospels. Barker's horror will make your worst nightmares seem like bedtime stories. The Gospels are coming.--amazon.com